SOA-Based Digitalisation of the Jakarta Metropolitan Police’s ICT Services for the Integrity of the Indonesian National Police’s Internal Services - Oktavio Jati Moris Pereira; Anita Ratnasari (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
Internal Information and Communication Technology (ICT) services within the Jakarta Metropolitan Police have traditionally relied on manual, fragmented processes, resulting in data duplication, delayed reporting, and weak accountability in IT asset management. This study aims to digitize these internal technical services and enhance organizational integrity by developing a centralized web-based application using a Service-Oriented Architecture (SOA). Employing a descriptive qualitative approach, data were gathered through observation, interviews, and documentation to map and restructure existing business workflows. The resulting system, Lantik PMJ, was built using CodeIgniter 4, MySQL, and Bootstrap 4 to integrate modular services for IT equipment loans, network installations, device repairs, and comprehensive asset lifecycle tracking. Black-box testing was conducted to validate system functionality across tiered, role-based access levels. The results demonstrate that the SOA-based application successfully replaces informal communication channels with a structured workflow, providing real-time service tracking, automated PDF reporting, and proactive return-delay monitoring for IT assets. All tested functional scenarios passed successfully, confirming the system’s reliability and readiness for operational deployment. Ultimately, this digital transformation significantly improves operational efficiency, transparency, and internal accountability, serving as a foundational model for the broader modernization of the Indonesian National Police’s internal support infrastructure.